Enhancement of Online Education to the Teaching Paradigm: Taking Academic Medical Postgraduate Cultivation as an Example - Su, Bin (Frontiers in Medicine, 2022)
Background: The COVID-19 pandemic posed enormous challenges to postgraduate teaching in 2020. Large-scale and continuous online teaching explorations were introduced to cope with this difficult situation, which incidentally shifted the paradigm of postgraduate teaching. Purpose: A review of the online teaching of local medical schools for postgraduates was performed to identify the success factors in realizing the practice. Methods: We retrieved medical postgraduate online teaching publications mainly from the local database, the China National Knowledge Infrastructure (CNKI), via the keywords stated below and then performed a retrospective analysis. Results: We analyzed key success factors in improving online learning engagement that were considered exclusive to offline classroom teaching, including emotional interaction, the immediacy of communication, and enthusiasm for participation. With these positive effects, the integration of online and offline teaching advantages is beneficial for the initiative of academic medical postgraduates and promotes the construction and development of postgraduate education. Conclusion: Online education can overcome the limitations of time, space, and teaching frequency, with great advantages in terms of flexibility and mobility over traditional classroom teaching. It can effectively cope with difficulties in the education of academic medical postgraduates in challenging times. In the post-pandemic era, blended online and offline teaching approaches continue and will become the new normal pedagogy for the training of postgraduate students.